2017
DOI: 10.1001/jamaoto.2016.2724
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based vs Traditional Operating Room Management of Recurrent Respiratory Papillomatosis

Abstract: There were no sex or age differences between patients with RRP treated in the office compared with those treated in the OR. Patients with earlier age at diagnosis of RRP and greater disease severity were more likely to be managed in the OR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…As has been observed with other office‐based laryngology procedures, procedure completion rate was high. This was despite several patients either having a diagnosis of generalized anxiety disorder or self‐reporting anxiety related to procedures.…”
Section: Discussionsupporting
confidence: 74%
“…As has been observed with other office‐based laryngology procedures, procedure completion rate was high. This was despite several patients either having a diagnosis of generalized anxiety disorder or self‐reporting anxiety related to procedures.…”
Section: Discussionsupporting
confidence: 74%
“…This is similar to what Tatar et al found, as RRP patients who underwent an operating room procedure had higher Derkay scores. 3 Another complicating factor of our study is that some patient responses did not match the corresponding objective data. For example, patients self-reported that the frequency with which they underwent each type of procedure was similar.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, the mean Derkay score for ALP was 8.26. The mean found for this group in the literature was 10.8 for patients operated on in an outpatient clinic, and 13.9 for patients operated on in a surgical center, where the choice of treatment in a surgical center was determined by the extent of the disease . In ALP, there is a directly proportional relationship between the Derkay score and the quality of life score related to voice (VHI‐10); that is to say, the higher the Derkay score, the more aggressive is the disease, and the higher the VHI‐10 score, the worse is the quality of life related to voice .…”
Section: Discussionmentioning
confidence: 96%
“…The mean found for this group in the literature was 10.8 for patients operated on in an outpatient clinic, and 13.9 for patients operated on in a surgical center, where the choice of treatment in a surgical center was determined by the extent of the disease. 24 In ALP, there is a directly proportional relationship between the Derkay score and the quality of life score related to voice (VHI-10); that is to say, the higher the Derkay score, the more aggressive is the disease, and the higher the VHI-10 score, the worse is the quality of life related to voice. 25 The present study did not evaluate VHI-10; however, a change in voice was observed in all the juvenile patients in the most aggressive cases, and in all the adult patients, due to the significant involvement of the vocal cords.…”
Section: Discussionmentioning
confidence: 99%